Analisa Kinerja Keuangan Untuk Keputusan Pemberian Kredit Pada Bank BRI Kelutum Pino Raya - Arfeny Oktantia Mariena; Neri Susanti; Nenden Restu Hidayah (Jurnal Multidisiplin Dehasen (MUDE), 2023)
This study uses descriptive qualitative research methods. Researchers find knowledge that describes the outline of the position, organizational structure, vision and mission, as well as what is required in writing. Data collected from respondents' responses can be used as research information. Sources of data were obtained from customers and Bank BRI Kelutum Pino Raya with the required documents complete. Two types of data were collected in this study: primary data and secondary data. Data collection techniques through observation, interviews and documentation. This study aims to determine the joint effect of Financial Performance Analysis on Credit Provision Decisions at BRI Kelutum Pino Raya Bengkulu Selatan. From the discussion above, it can be concluded that the credit application submitted is accepted by several factors, namely:1. Collateral submitted by customers is in accordance with the amount of credit they want.2 Checking BI Checking which shows the customer has smooth credit and is not on the Blacklist. 3 The customer has a business license. 4 Customers also provide honest data in conducting interviews with BRI. Analysis of financial performance based on liquidity, profitability and solvency